2010
DOI: 10.1093/jaoac/93.1.277
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ethoxyquin by High-Performance Liquid Chromatography with Fluorescence Detection and Its Application to the Survey of Residues in Food Products of Animal Origin

Abstract: An analytical method using HPLC with fluorescence detection (HPLC-FL) has been developed and applied for the survey of residue levels of ethoxyquin in a variety of food products of animal origin. HPLC was performed using a silica octadecylsilane column, butylhydroxytolueneacetonitrilewater (0.05 + 800 + 200, v/v/v) mobile phase, and detection at excitation and emission wavelengths of 370 and 415 nm, respectively. HPLC/MS was used to confirm whether a chromatographic peak was ethoxyquin. The LOQ of the foods wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The levels of the parent compound (EQ) in meat of farmed animals are usually lower than MRL (Maximum Residue Level) [ 20 , 84 ], but EQ oxidation products are usually not controlled. It was shown that EQDM and other EQ residues can be present in different animal tissues [ 23 , 24 , 26 , 28 , 37 ].…”
Section: Food Safety Aspectmentioning
confidence: 99%
“…The levels of the parent compound (EQ) in meat of farmed animals are usually lower than MRL (Maximum Residue Level) [ 20 , 84 ], but EQ oxidation products are usually not controlled. It was shown that EQDM and other EQ residues can be present in different animal tissues [ 23 , 24 , 26 , 28 , 37 ].…”
Section: Food Safety Aspectmentioning
confidence: 99%
“…Various procedures for the extraction of EQ and some of its oxidation products have been described in the literature, mostly comprising simple liquid extraction of homogenized samples using organic solvents , or the QuEChERS protocol. , Other methods make use of solid-phase extraction or include a further saponification step with sodium hydroxide for enhanced matrix disruption prior to liquid extraction. , However, because of the high fat content of certain fish species like salmon, the biggest challenge remains the efficient separation of the most lipophilic analyte, EQDM, from disturbing matrix components.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, GC-FID and GC-MS used to be the methods of choice some decades ago, , despite the drawback of the low temperature stability of EQ, which quickly degrades to DMEQ at the temperatures applied in the injector and the column oven during GC analysis . Today, LC-based methods can be considered state-of-the-art. ,,,, Moreover, the dihydroquinoline moiety of EQ and EQDM as well as the quinoline in DMEQ make these compounds excellent fluorophores, allowing for selective and sensitive detection using a fluorescence detector after LC separation (LC-FLD). The reported drawback that QI can hardly be detected by LC-FLD, as its quinone imine structure shows only weak fluorescence, can easily be overcome by postcolumn reduction of QI to DEQ (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations